Naphthoquinone based chemosensor 2-(2 `-aminoethylpyridine)-3-chloro-1,4-naphthoquinone: detection of metal ions, X-ray -crystal structures and DFT studies - Patil, Amit; Ware, Anuja P.; Bhand, Sujit; Chakravarty, Debamitra K.; Gonnade, Rajesh G.; Pingale, Subhash S.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2016)
Naphthoquinone based Chemosensor 2; 2-(2'-aminoethylpyridine)-3-chloro-1,4-napthoquinone have been synthesized and characterized. Chemosensor 2 crystallizes in the orthorhombic space group Pbcn and shows extensive intramolecular as well as intermolecular hydrogen bonding interactions. Each molecule of Chemosensor 2 showed interaction with five neighboring molecules via C-H center dot center dot center dot N, N-H center dot center dot center dot N, C-H center dot center dot center dot Cl and C-H center dot center dot center dot O interactions. Slipped pi-pi stacking interaction was observed in adjacent quinonoid and benzenoid rings. Chemosensor abilities of Chemosensor 2 ligand have been evaluated with metal ions viz. Cu2+, Ni2+, Zn2+, Co2+, Fe3+, Mn2+, Cr3+, Hg2+, La3+ and Cd2+ in methanol, methanol-water mixture and in presence of mild base triethylamine. Stoichiometry of Chemosensor 2 with metal ions such as Cu2+, Ni2+, Zn2+ and Co2+ ions was determined by Jobs method in methanol and were found as 1:1 for Cu2+ and 2:1 for Ni2+, Zn2+ Co2+. The variation in the metal ligand ratio is observed in aqueous media for Cu2+. Chemosensor 2 can be used selectively for naked eye detection of Cu2+ ions. The association constant obtained in methanol shows the trend Cu2+>Ni2+>Co2+. Cu2+ and two (Ni-1 and Ni-2) Ni2+ complexes were synthesized. Ni-2 complex showed coordination of Chemosensor 2 ligands was through pyridine nitrogen's only. The Chemosensor 2 and its deprotonated forms in methanol, water and triethylamine were also studied by TD-DFT studies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Chemosensor; hydrogen bonding; Naphthoquinone; pi-pi stacking; TD-DFT

Amphiphilic polypyridyl ruthenium complexes: synthesis, characterization and aggregation studies - Bhand, Sujit; Lande, Dipali N.; Pereira, Eulalia; Gejji, Shridhar P.; Weyhermueller, Thomas; Chakravarty, Debamitra; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Polyhedron, 2019)
{Synthesis and characterization of five amphiphilic ruthenium(11) complexes of the type [Ru(Cn)(3)]center dot(PF6)(2) (Cn = 4,4'-dialkyl-2,2'-bipyridine
Keywords: 2; 2 `-bipyridine; Aggregation; Amphiphilic ligand; Metallosurfactant; Ruthenium complexes